Recycling of cathode material from spent lithium-ion batteries - Dragana V. Medić; Mile D. Dimitrijević; Boban R. Spalović; Snežana S. Milić; Ivan N. Đorđević (Zaštita Materijala)
In this paper the structure and principle of the operation of Li-ion batteries is presented. A brief overview of cathodic and anodic materials development, as well as the requirements that separator and electrolyte should fulfill in order to be used in Li-ion batteries are given. Also, all the stages in the process of recycling Li-ion batteries, with the special consideration of hydrometallurgical treatment of cathode material, and the valorization of lithium and cobalt are described.